Pie in the sky - Ehlert, Lois. (Orlando : Harcourt, 2004)
A father and child watch the cherry tree in their back yard, waiting until there are ripe cherries to bake in a pie. Includes a recipe for cherry pie.
Keywords: Cherry -- Fiction; Trees -- Fiction; Pies -- Fiction; Father and child -- Fiction